Indian Brachytherapy Society Guidelines for radiotherapeutic management of cervical cancer with special emphasis on high-dose-rate brachytherapy - Mahantshetty, Umesh; Gudi, Shivakumar; Singh, Roshni; Sasidharan, Ajay; Sastri, Supriya (Chopra); Gurram, Lavanya; Sharma, Dayanand; Ganeshrajah, Selvaluxmy; MG, Janaki; Badakh, Dinesh; Basu, Abhishek; James, Francis; et al. (Journal of Contemporary Brachytherapy, 2019)
Brachytherapy (BT) for locally advanced cervical cancer is vital for optimal outcomes. There is heterogeneity in brachytherapy treatment practice for cervical cancer across India. In an attempt to standardize various processes involved in cervical cancer brachytherapy, the expert members of the Indian Brachytherapy Society (IBS) developed a document related to radiation therapy treatment of cervical cancer with special emphasis on brachytherapy. The guidelines are based on high quality clinical evidence, expert opinion and consensus wherever evidence was lacking. The document provides a guide for external beam radiation and details of all the processes involved in high-dose-rate (HDR) brachytherapy including patient selection, preparation, principles and technique of BT applications, target and normal tissue definition, dose prescriptions, BT planning, reporting parameters, common complications of BT and their management, scope for research, etc. In summary, we present here practical tips and tricks, recording and reporting of cervical cancer brachytherapy, which can be implemented in various clinical environments and forms the basis of this report.